Coupling wastewater valorization with sustainable biofuel production: Comparison of lab- and pilot-scale biomass yields of Chlorella sorokiniana grown in wastewater under photoautotrophic and mixotrophic conditions. (August 2022) - Qurat-ul-Ain,; Javid, Arshad; Ali, Shahid; Hasan, Ali; Senthilkumar, Natarajan; Ranjitha, Jambulingam; Hussain, Ali
Abstract: Microalgae are the important biofuel precursors and their economic cultivation can be boosted under mixotrophic (MT) conditions while employing different industrial wastewaters containing organic carbon. In the current research, the quantitative analysis of microalgal biomass production under MT and photoautotrophic (PT) cultivation conditions both at lab and pilot scales was studied. For the purpose, a pre-identified microalgal species Chlorella sorokiniana was cultivated mixotrophically and photoautotrophically at lab and pilot scales. Artificially prepared wastewater containing 2% (w/v) sugarcane molasses was used for MT cultivation. However, for PT cultivation, atmospheric CO2 was the only carbon source. After 15 days of aerobic incubation, microalgal biomass was harvested and analyzed for biomass productivity. Cultivation conditions and cultivation scale posed significant and non-significant impact, respectively on biomass productivities. However, biomass productivity was comparatively higher for the biomass raised under MT conditions at lab scale. The recorded values of biomass productivity were 88.75 ± 9.51 and 127.68 ± 7.91 mg L −1  d −1 for the biomass raised at lab scale under PT and MT conditions, respectively. Pilot-scale cultivation depicted biomass productivities as 83.49 ± 7.87 and 124.88 ± 3.76 mg L −1  d −1 under PT and MT conditions, respectively. High biomass production under MT conditions may suggest the elevated production of biofuels from microalgae. Future studies on biomass production while utilizing different industrial wastewaters at pilot scale and in open raceway ponds are needed for viable production of microalgae-based fuels. Graphical abstract: Image 1 Highlights: Chlorella sorokiniana was exploited for its biomass productivity under photoautotrophic and mixotrophic culture conditions. Artificially prepared organic-carbon added wastewater was used for mixotrophic cultivation. Higher biomass productivity with concomitant remediation of wastewater was achieved under mixotrophic conditions.